DAMPAK KOMPETENSI WIDYAISWARA, PERUBAHAN KURIKULUM, SARANA PRASARANA TERHADAP KEPUASAN PESERTA DIKLATPIM III DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI JAWA BARAT - Dede Pandaswita (Lembaga Administrasi Negara, 2020)
The purpose of this study was to determine the impact of widyaiswara competencies, changes in curriculum and infrastructure to training participants' satisfaction in the Human Resources Development Agency of West Java Province. In this study all the training participants of PIM III in the Human Resources Development Agency budget for 2017 and 2018 amounted to 370 people. The total sample is 192 people, the sampling technique uses the stratified random sampling method. The location of this study is in BPSDM, West Java Province, located on Jl. Colonel Maturi KM 3.5 No. 11, West Java. The analysis technique uses Partial Least Square (PLS) Software. The results showed that the widyaiswara's competence had a significant impact on participant satisfaction. Changes in education and training curriculum have a significant impact on participant satisfaction. Education and training infrastructure facilities have a significant impact on participants' satisfaction in education and training. Widyaiswara's competencies, curriculum changes and infrastructure facilities had an impact on the satisfaction of Diklatpim III participants in the Human Resources Development Agency of West Java Province. In general, this study concluded that the new pattern of education and leadership training according to the Head of Regulation of the State Administration Agency Number 19 of 2015 received positive responses from training participants and mentors, such as direct supervisors of participants in building high performance in institutions and training participants.Keywords : widyaiswara competence, curriculum change, facilities and infrastructure, training participants satisfaction